Three-Pole Tunable Filters with High Rejection using Mixed Quarter-Lambda and Asymmetric Half-Lambda Resonators - Zhao, Zhiyuan; Chen, Jiang; Yang, Lin; Chen, Kunhe (Společnost pro radioelektronické inženýrství, 2014)
A novel three-pole tunable bandpass filter using varactor-loaded quarter-wavelength combline and asym-metric half-wavelength resonators is proposed in this paper. A nearly constant 3-dB absolute bandwidth is 150 ± 13 MHz (10.7%~6.9% fractional bandwidth) within the tuning range of 1.4-2.0 GHz (42.8%). The filter is designed on a Rogers substrate with relative permittivity 2.2 and h=1 mm with its insertion loss varying from 3.6 dB to 2.8 dB and return loss better than 10 dB over the entire tuning range. The creation of two transmission zeros near the passband edges is analyzed by the even-odd-method. By using dissimilar resonators, the proposed tunable filter could obtain > 33 dB rejection levels at the second harmonics. The measured results show good agreement with the simulated ones.
Keywords: Three-pole tunable filters; combline resonators; modified combline resonators; constant absolute bandwidth (CABW); transmission zeros (Tzs); varactor-tuned